2020
DOI: 10.1038/s41598-020-70194-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multifunctional TANI/Cu2O/Ag nanocomposite for environmental abatement

Abstract: During past decade, the ternary nanocomposite is ubiquitous in nanotechnology. Herein, a simple fabrication of cuprous oxide (cu 2 O) and silver (Ag) nanoparticles into Tetraaniline (TANI) matrix by in situ-polymerization approach to attain Tetramer-Metal Oxide-Metal (TANI/Cu 2 O/Ag, shortly TCA) ternary composite was reported firstly. The synthesized materials were further characterized by a series of instrumental techniques to understand its structure, morphology and thermal properties. This nanocomposite sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It has wide range of properties like novel electronic properties, elastic properties and extraordinary electronic conductivity, which suggested that this material can be used for removal of dyes [32][33][34]. In recent years, various metal and metal oxides nanoparticles (Fe 2 O 3 , Ag, Cu 2 O, NiO) and conducting polymers (PANI, PP, PEDOT) have been utilized as effective adsorbents towards the adsorption of various dyes [35,36]. Rajumon et al studied the adsorption of Basic Fuchsin (BF) and Methylene Blue (MB) on rGO.…”
Section: Introductionmentioning
confidence: 99%
“…It has wide range of properties like novel electronic properties, elastic properties and extraordinary electronic conductivity, which suggested that this material can be used for removal of dyes [32][33][34]. In recent years, various metal and metal oxides nanoparticles (Fe 2 O 3 , Ag, Cu 2 O, NiO) and conducting polymers (PANI, PP, PEDOT) have been utilized as effective adsorbents towards the adsorption of various dyes [35,36]. Rajumon et al studied the adsorption of Basic Fuchsin (BF) and Methylene Blue (MB) on rGO.…”
Section: Introductionmentioning
confidence: 99%
“…The good adsorptive removal of MG dye from textile industry effluents offers the possibility of using PTP/PR nanocomposite in environmental wastewater treatment application. 59 The efficacy of PTP/ PR nanocomposite towards MG dye removal in samples, prepared in normal tap water and deionized water depicted more or less similar % adsorption under optimized conditions Figure 9A. The viability of selective adsorption using PTP/PR were studied by taking Rhodamine as cationic dye, Congo red and Methyl orange as anionic dyes.…”
Section: Adsorption Studies Of Mg Dye In Real Time Samplesmentioning
confidence: 99%
“…This may be due to the concentration of dye increase, more dye concentration will be available for excitation and energy transfer [4] which enhances the degradation percentage, but above the limit due to the fact that at the higher concentration dye start covering the active surface of photocatalyst as a blanket and intercepting from light intensity [15] that decreases degradation. The synthesized reduced graphene oxide based metal sulfide composite showed better photocatalytic activity due to increases in the number of impurity energy levels between the VB and CB which helps for the generation of more electron-hole pairs, thus decreasing the recombination of photogenerated holes and electrons by reduced graphene oxide [1][2][3] to eliminate the harmful effect of defect bands.…”
Section: Effect Of Dye Initial Concentrationmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) predominantly photocatalysis have raised a promising solution for the degradation of harmful organic pollutants and microorganisms in polluted water [1]. US EPA (Environmental Protection Agency) declared that 4nitrophenol (4-NP) has been recognized as a nonbiodegradable pollutant owing to its great solubility and stability in water media, also accumulated on the surface of the soil with no degradation [2].…”
Section: Introductionmentioning
confidence: 99%